Fate of antibiotics present in a primary sludge of WWTP during their co-composting with palm wastes. (1st February 2019) - Khadra, Ahmed; Ezzariai, Amine; Merlina, Georges; Capdeville, Marion-Justine; Budzinski, Hélène; Hamdi, Hassan; Pinelli, Eric; Hafidi, Mohamed
Highlights: Antibiotics dissipation depended on the stage of composting. Ciprofloxacin and ofloxacin still persistent after sludge composting. Fluoroquinolones persistence limits a safe use of the composted sludge in agricultural soils. Abstract: Antibiotics persistence in the primary sludge can contribute to the emergence of these molecules in the environment and limit the agricultural recycling of sludge without any preliminary treatment. Composting is a widely used process for recycling sludges and then can contribute to the antibiotics removal. However, little interest is actually given to the evaluation of the persistence of some antibiotics families after the sludge co-composting and more particularly to the final compost valorization. In this work, antibiotics concentrations of βeta-lactams, Macrolides, Lincosamide, Tetracyclines, Sulfonamides and Fluoroquinolones were checked in the primary sludge of the wastewater treatment plants (WWTP) of Marrakesh (Morocco) before its co-composting. The results showed a final high amount of the fluoroquinolones family (4.21 and 2.92 μg/kg DM for Ciprofloxacin and Ofloxacin respectively) compared to the other studied families. To assess the fate of antibiotics, the primary sludge and palm waste were windrowed and composted during 120 days. The final compost showed a high level of organic matter decomposition (52%) and a C/N ratio of 12 which insure the compost quality. The assessment of antibiotics concentrations during co-composting showed that clarithromycin is more degraded particularly during the stabilization stage (43%), the degradation of lincomycin and tetracyclines is more significant during the maturation stage (36 and 75% respectively). Ampicillin and trimethoprim were degraded all along the process of co-composting (46 and 35% respectively). By the way, the persistence of the fluoroquinolones family was observed. This persistence could be a limiting key factor for the composted sludge valorization. So, more knowledge is needed to understand fluoroquinolones behavior and, then, to optimize their composting conditions.